ANALISIS PARTISIPASI WANITA DALAM PELESTARIAN TENUN IKAT SUKU DAYAK DESA DI RUMAH BETANG ENSAID PANJANG SINTANG - Clara Octaviany; Yohanes Bahari; Amrazi Zakso (Universitas Tanjungpura, 2020)
AbstractThe title of this thesis is Analysis of Women's Participation in the Preservation of Dayak Village Bonds in the Betang Ensaid Panjang House of Sintang District. The general problem in this study is